Reduction of Au(III) by a β-cyclodextrin polymer in acid medium. A stated unattainable reaction. (1st November 2017) - Martin-Trasanco, Rudy; Cao, Roberto; Esparza-Ponce, Hilda Esperanza; Montero-Cabrera, Maria Elena; Arratia-Pérez, Ramiro
Highlights: β-Cyclodextrin polymer reduces Au(III) to Au 0 in acid medium. A mechanism to explain the low rate of reaction is proposed. Primary alcohols are oxidized to carboxylic acid. Gold nanoparticles are capped with dimers of the polymer. Abstract: Gold nanoparticles (AuNPs) can be prepared from the reduction of Au(III) with cyclodextrins acting as both, reducing and capping agent. It has been stated that a basic medium (pH = 9–12) is a mandatory condition to achieve such reduction. We demonstrated, for the first time, the reduction of Au(III) by a crosslinked β-cyclodextrin-epichlorohydrin polymer (βCDP) in acid medium (pH ∼3). The coordination of Au(III) to the βCD in βCDP polymer required a βCD:[AuCl4 ] − ratio of 4:1. The same ratio was necessary to achieve a 50% of the reduction of Au(III) to Au 0 within the first 24 h of reaction. During this initial time, the reaction showed a concentration-dependent reduction rate while for longer times the reduction rate was diffusion-dependent. An overall mechanism to explain this dependency has been proposed. The 13 C NMR spectrum identified the oxidation of the COH groups to carboxylic ones by recording a signal at 175.6 ppm. Gold nanoparticles cores (AuNPs) with a diameter of 34.2 ± 7.7 nm, determined by Transmission Electron Microscopy (TEM), was prepared by refluxing HAuCl4 in an aqueous solution of βCDP. The AuNPs core was capped by dimers of the βCDP polymer as determined by Dynamic Light Scattering measurements.